The effect of using multimedia super overlap (Hyper Media) in the learning and keeping to some balance beam skills in the women's artistic gymnastics - Shihab, Zahra; Saleem, Suzan; Saleh, Ayad (Journal of Physical Education, 2014)
The effect of using multimedia super overlap (Hyper Media) in the learning and keeping to some balance beam skills in the women's artistic gymnastics The aim of this study is to prepare the Intermediate learning by use super overlap(Hyper Media) and to identify the effect of their use in the learning and keeping to some balance beam's skills in the women's artistic gymnastic, as well as to identify the best group between the groups study in the learning and retention of skills in this study, the researchers used the experimental method and included a subject of the study on students third class in the Physical Education College University of Baghdad , and three groups and using the lottery was selected students class (E) represented for the experimental group, and students they are class (T) the control group, they are 20 students per group used learning with a multimedia super overlap (Hyper media) prepared by the researchers, was used, the control group the traditional method, and after conducting pre-test and post- test and retention test, the researchers used the Statistical package for Social Sciences (SPSS) to deal with the results of their research, which included (mean, standard deviation, T.test for symmetric subject and nonsymmetrical, test of magnitude of saving memory). The researchers found the most important conclusions: the presentation skills (under study) by use of multimedia super overlap (Hyper Media) by use automated computer and the monitor gives a positive effect in facilitating learning and retention by what the student see display right performance skills as well as slow motion capability which provided a good opportunity to know the performance skills and speed absorbed